Growth Performance of Poultry Genotypes under Intensive Management System - Satish Jadhao,; AJ Mayekar,; Shalu Kumar,; BG Desai,; JS Dhekale, (Journal of Livestock Biodiversity, 2025)
The present experiment was conducted at Poultry Unit, Department of Animal Husbandry and Dairy Science, Dr. B. S. Konkan Krishi Vidyapeeth Dapoli, Maharashtra to assess the comparative growth performance and feed efficiency of poultry genotypes. The experiment was carried out on three different types of poultry genotypes viz., -Vanaraja (T1), Giriraja (T2) and Rhode Island Red (T3). For this experiment, 150 day old chicks were divided in five replications and each replicate have 10 birds. Results showed that Giriraja birds gain significantly higher daily body weight gain, weekly body weight gain and total body weight gain with superior feed conversion efficiency compared to Vanaraja and Rhode Island Red. The benefit cost ratio (B:C ratio) higher achieved by Giriraja birds. From the results of present investigation, it can be suggested that the rearing of Giriraja poultry birds are more beneficial and efficient than Vanaraja and RIR in Konkan Agro-climatic condition of Maharashtra.